Negotiating the Transnational Workplace: Indian Computer Professionals in Australia. - Lakha, Salim (Journal of Intercultural Studies, 2005)
Academics and journalists have responded in various ways to the recent influx of Indian computer professionals into Australia. Though references to their inflow on temporary visas are frequent, there is as yet no attempt to examine in detail their experiences in the workplace. This paper considers the workplace experiences of Indian computer professionals in Melbourne in the context of the discussion on transnational social spaces. It deals with a specific case study involving employees from an Indian subsidiary of an Australian financial institution who work here on temporary visas. The paper looks at three areas of their professional lives: communication, relations with co-workers and satisfaction in the workplace. It reveals that their presence in the transnational workplace is marked by contested identity, concerns about security of employment and different understandings of what constitutes effective communication. The paper demonstrates that the emergence of transnational social spaces has complex and contradictory outcomes.